Crack healing of ferrosilicochromium-filled polymer-derived ceramic composites. Issue 6 (June 2018) - Schlier, Lorenz; Fu, Zongwen; Harris, Joe; Greil, Peter; Travitzky, Nahum
Abstract: In this study, SiOC/FeSiCr/SiC-ceramics were derived by using polymethylsilsesquioxane as a polymeric precursor and FeSiCr (iron-chromium-silicide) and SiC powders as ceramic fillers in a polymer-extrusion process followed by pyrolytic conversion in a nitrogen atmosphere. The crack healing properties of the ceramic in an oxidising atmosphere were subsequently investigated. The SiOC/FeSiCr/SiC-ceramics showed crack closure and strength recovery behaviour after oxidation treatments in air from 600 to 1300 °C with various holding times from 2 to 1000 min. The crack healing mechanisms at different oxidation temperatures and with various dwell times are discussed.